Multi-level variations of lateral habenula in depression: A comprehensive review of current evidence - Zhang, Guang-Ming; Wu, Hong-Yun; Cui, Wen-Qiang; Peng, Wei (Frontiers in Psychiatry, 2022)
Despite extensive research in recent decades, knowledge of the pathophysiology of depression in neural circuits remains limited. Recently, the lateral habenula (LHb) has been extensively reported to undergo a series of adaptive changes at multiple levels during the depression state. As a crucial relay in brain networks associated with emotion regulation, LHb receives excitatory or inhibitory projections from upstream brain regions related to stress and cognition and interacts with brain regions involved in emotion regulation. A series of pathological alterations induced by aberrant inputs cause abnormal function of the LHb, resulting in dysregulation of mood and motivation, which present with depressive-like phenotypes in rodents. Herein, we systematically combed advances from rodents, summarized changes in the LHb and related neural circuits in depression, and attempted to analyze the intrinsic logical relationship among these pathological alterations. We expect that this summary will greatly enhance our understanding of the pathological processes of depression. This is advantageous for fostering the understanding and screening of potential antidepressant targets against LHb.